2023
DOI: 10.1007/s42729-022-01104-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Effects of Potassium Fertilization Rate and Application Time on Growth and Grain Yield of Wheat (Triticum aestivum L.) Plants Grown Under Cd-Contaminated Saline Soil

Abstract: Potassium is an essential macronutrient, where its availability regulates numerous biochemical, phenological, and physiological responses in plants. Synchronizing potassium supply with plant demand is a key factor to enhance growth and grain production of wheat grown in cadmium-contaminated saline soils. Field experiments were conducted in El Fayoum province, Egypt, between latitudes 29° 02′ and 29° 35′ N and longitudes 30° 23′ and 31° 05′ E, during the cropping seasons of 2017–2018 and 2018–2019 to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…Conversely, the absence of K supplementation resulted in deformities in vegetative growth and reduced biomass yield in wheat crops. These results are consistent with the findings of numerous other researchers in this field, including (Guo et al 2019;El-Mageed et al 2023;El-Nahas et al 2019). They found that K fertilization had increased the yield of wheat growth and development.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the absence of K supplementation resulted in deformities in vegetative growth and reduced biomass yield in wheat crops. These results are consistent with the findings of numerous other researchers in this field, including (Guo et al 2019;El-Mageed et al 2023;El-Nahas et al 2019). They found that K fertilization had increased the yield of wheat growth and development.…”
Section: Discussionsupporting
confidence: 93%
“…This consistent performance underscores the potential of PN as a highly effective fertilizer for garlic cultivation. On the other hand, a lack of potassium adversely affects the growth and expansion of garlic leaves, resulting in hindered development and stunted growth (El-Mageed et al, 2023). Indeed, nitrogen plays a pivotal role in plants as it is utilized for the synthesis of crucial components such as amino acids, chlorophyll, enzymes, and DNA (Stein and Klotz, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It can improve various aspects such as SPAD (chlorophyll content), photosynthesis, transpiration, and fruit yield (Yang et al, 2017). Conversely, a deficiency of potassium negatively impacts the plant's leaf growth and expansion, leading to stunted development (El-Mageed et al, 2023). Fulvic acid is known to contain nitrogen, and the quantity of nitrogen in fulvic acid varies based on the parent material from which it is derived (Winkler and Ghosh, 2018).…”
Section: Discussionmentioning
confidence: 99%